A Sustainable Paperless Online System (SPOS) for Engineering Quality in Teaching: Koya University as a Case Study - Yahya, Salah I.; Rostam, Dilan M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2015)
Rapidly advancing computer based technologies offer many possibilities for innovation in educational and administrative assessment tasks which allow for a reliable real time reporting and feedback process. This paper considers the requirements for teacher assessments to become an accurate and reliable process. As a case study, the challenges of implementing such a system at Koya University have been considered. This paper examines how a paperless online system can support faculties’ efforts for improving sustainable quality in learning and up-to-date assessment techniques. The proposed sustainable paperless online system (SPOS) uses Google Applications for Education that have been adopted at Koya university as a communications and collaboration medium to enhance its teaching quality. Such a system may enhance security, transparency and ease of use while consuming less time and resources and promoting green practice. The work throughout this paper explains how the initiative is engineered for achieving and monitoring a better quality in teaching.